Innovative Models to Revive the Global Economy : Proceedings of the 3rd International Conference on Economics and Social Sciences - Alina Mihaela Dima (Sciendo, 2020)
The International Conferences on Economics and Social Sciences (ICESS)organized by Bucharest University of Economic Studies provide an opportunity for all those interested in Economics and Social Sciences to discuss and exchange research ideas. The papers presented at the Conference are available online in the Conference Proceedings series (ISSN 2704-6524): Volume 2019 Collaborative Research for Excellence in Economics and Social Sciences, ISBN 9788366675322 Volume 2020 Innovative Models to Revive the Global Economy, ISBN 9788395815072 Volume 2021 Resilience and Economic Intelligence Through Digitalization and Big Data Analytics, ISBN 9788366675704 Volume 2022 Fostering recovery through metaverse business modelling, ISBN 9788367405072 This conference provides an opportunity for all those interested in Economics and Social Sciences to discuss and exchange research ideas. We welcome both empirical and theoretical work that is broadly consistent with the conference'general theme. Especially, researchers, PhD students and practitioners are invited to submit papers on the topics related to new models in entrepreneurship and innovation, sustainability and education, data science and digitalization, marketing and finance, Fintech & Insurtech etc. that will develop innovative instruments for countries, businesses and education. The innovative models for sustainable development aim to ensure simultaneous economic development, social development, and environmental protection, to achieve a higher quality of life for all people and protect all living beings and the planet. The main topics of the conference are focused on but not limited to the following sections: Fintech & Insurtech - towards a sustainable financial environment The role of innovation in public and private organizations Financial perspectives in turbulent times Global Challenges for Agri-Food Systems and Sustainable Development Economic Policies for Non-Cyclical Crises Education for Sustainable Development: impact of universities on society Marketing and Sustainability The role of accounting in Sustainable Development Global world after crisis: towards a new economic model Sustainability for future business Current challenges within demographic data: measurement, collection, retrieval, analysis and reporting Scientific CommitteeACELEANU Mirela, Bucharest University of Economic Studies, RomaniaALBU Lucian, Academia Romana, RomaniaANGHEL Ion, Bucharest University of Economic Studies, RomaniaARROYO GALLARDO Javier, Complutense University of Madrid, SpainAUSLOOS Marcel, Leicester University, United KingdomBEGALLI Diego, University of Verona, ItalyBELLINI Francesco, Sapienza University of Rome, ItalyBRATOSIN Ștefan, Universite Montpellier 3, FranceCABANIS Andre, Universite Toulouse 1 Capitole, FranceCASTERAN Herbert, EM Strasbourg University, FranceCENȚIU Silvian, Retina Communications, San Francisco, USACERQUETI Roy, Sapienza University of Rome, ItalyCHAVEZ Gilbert, Globis University Tokyo, JapanCOSTICÃ Ionela, Bucharest University of Economic Studies, RomaniaCOX Michael, London School of Economics, England, UKD'ASCENZO Fabrizio, Sapienza University of Rome, ItalyDIMA Alina Mihaela, Bucharest University of Economic Studies, RomaniaDÂRDALÃ Marian, Bucharest University of Economic Studies, RomaniaDU